2003
DOI: 10.4049/jimmunol.170.10.4933
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CD8+ T Cells Undergoing Primary and Secondary Responses to Infection in the Same Host

Abstract: Naive Ag-specific CD8+ T cells expand, contract, and become memory cells after infection and/or vaccination. Memory CD8+ T cells provide faster, more effective secondary responses against repeated exposure to the same pathogen. Using an adoptive transfer system with low numbers of trackable nontransgenic memory CD8+ T cells, we showed that secondary responses can be comprised of both primary (naive) and secondary (memory) CD8+ T cells after bacterial (Listeria monocytogenes) and/or viral (lymphocytic choriomen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
84
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(100 citation statements)
references
References 37 publications
15
84
0
Order By: Relevance
“…CD8 ϩ T cells against the same epitope have been previously shown to compete for access to APCs (41)(42)(43)(44), and our results support this notion. However, other experimental models using peptide-loaded DCs to stimulate CD8 ϩ T cells have reported little competition for access to APCs (45).…”
Section: Discussionsupporting
confidence: 81%
“…CD8 ϩ T cells against the same epitope have been previously shown to compete for access to APCs (41)(42)(43)(44), and our results support this notion. However, other experimental models using peptide-loaded DCs to stimulate CD8 ϩ T cells have reported little competition for access to APCs (45).…”
Section: Discussionsupporting
confidence: 81%
“…Using a dual adoptive transfer system, we directly compared the expansion of memory CD8 ϩ T cells created in the absence or presence of TCDD in the same host. Given that the magnitude of a memory response is thought to be influenced by the primary CD8 ϩ T cell response (38,40,44,45), it is logical to hypothesize that impairment of the primary response by an immunosuppressive compound will lead to an insufficient recall response. However, we show in this study that this is not necessarily the case.…”
Section: Discussionmentioning
confidence: 99%
“…We and others previously showed that contraction of the secondary CD8 ϩ T cell response is prolonged compared with contraction of the primary CD8 ϩ T cell response, independent of host environment or duration of infection (17,47,48). To investigate the kinetics of primary vs secondary CD4 ϩ T cell responses and compare the kinetics of CD4 ϩ and CD8 ϩ T cell responses, day 70 memory T cells from rLM-OVA-immune B6.PL mice (Thy1.1 ϩ ) were transferred into naive B6 recipients (Thy1.2 ϩ ), and on 1 day post-transfer, recipient mice were infected with rLM-OVA.…”
Section: Kinetics Of Primary Vs Secondary Cd4 ϩ T Cell Response In Thmentioning
confidence: 99%